Media Convergence and Cultural Hybridity: Negotiating Traditional Ketoprak and Global Netflix in Indonesia’s Digital Landscape - Nolly Medya Putra (MD Research Center, 2026)
Media convergence between traditional art forms and global digital platforms has fundamentally reshaped cultural expression. This study examines this transformation in Indonesia, focusing on the interaction between the traditional Javanese art of Ketoprak and the global streaming service Netflix. Employing a qualitative approach with a literature study method, the research investigates how digital media not only alters patterns of cultural production and consumption but also renegotiates local values within a global landscape governed by algorithmic logic. The findings indicate that this interaction generates cultural hybridity, expanding representational spaces and enabling new cross-border cultural practices. However, the process also presents ethical and ideological challenges, including cultural commodification and the potential erosion of local values due to dominant global market logic. The study concludes that the success of cultural preservation in the digital era hinges on the ability of local communities to adapt creatively without losing their cultural identity, framing media convergence as a field of meaning negotiation between tradition, modernity, and algorithmic power.